1980
DOI: 10.1115/1.3230219
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Some Design Parameters of an Isolated Rotor on Inlet Flow Distortions

Abstract: A study of the effects of rotor-blade geometry, steady loading, and distortion wavelength on the distortion flow field upstream and downstream of an unstalled isolated rotor shows that the attenuation of the distortion as it passes through the rotor is a function of the blade stagger angle and the distortion-reduced frequency or the ratio of rotor blade spacing to the distortion wavelength s/l. Maximum attenuation occurs when s/l = 0.5 and increases with increasing stagger angle. Little influence of rotor inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The present investigations consider the combined effects of swirl and circumferential distortion. Most of the literature available till date on inlet flow distortion deals extensively on circumferential distortion alone (Colpin, 1979;Ehrich, 1957;Yocum and Henderson, 1980) and only recently few investigators have considered the combined effects of swirl and circumferential distortion. Flitcroft et al (1987) investigated the effect of inlet swirl on the propagation of total pressure distortion through a 3-stage fan without IGV.…”
Section: Clem Inlc7mentioning
confidence: 99%
“…The present investigations consider the combined effects of swirl and circumferential distortion. Most of the literature available till date on inlet flow distortion deals extensively on circumferential distortion alone (Colpin, 1979;Ehrich, 1957;Yocum and Henderson, 1980) and only recently few investigators have considered the combined effects of swirl and circumferential distortion. Flitcroft et al (1987) investigated the effect of inlet swirl on the propagation of total pressure distortion through a 3-stage fan without IGV.…”
Section: Clem Inlc7mentioning
confidence: 99%
“…It was concluded that an attenuation of 0.7 to 0.8 in velocity distortion is attainable and can be improved with lower reaction staging. In another study by Yocum and Henderson [8], it was shown that the attenuation of distortion as it passes through the rotor is a function of the blade stagger angle and the ratio of the rotor blade spacing to the distortion wave length. Plourde [9] concluded from his studies in a multistage compressor that the overall attenuation of both total pressure distortion and axial velocity distortion is dependent on the slope of the compressor characteristics.…”
Section: Introductionmentioning
confidence: 98%